Lymphatic Obstruction and Edema in Neonate due to Left Subclavian Central Venous Catheter - Klaas Koop; Dominique Valérie Clarence de Jel; Joppe Nijman; Barbara Peels; Ellis Peters (Case Reports in Pediatrics)
There are several causes of generalized edema in sick neonates. We describe two newborns that developed progressive and treatment-resistant generalized edema. We suggest this is due to impaired lymphatic flow from the thoracic duct as a result of a central venous catheter in the left subclavian vein.